Influence of Social Support and Self-Compassion on Student Happiness in the Pandemic Period - Salsabila Ananda Putri; Yufi Adriani (Jurnal Paedagogy, 2023)
This study aimed to analyze the impact of social support and self-compassion on students' happiness during a pandemic. This study used a quantitative approach with multiple regression analysis. The sample was taken using the non-probability sampling method (purposive sampling), consisting of 213 students living in JABODETABEK. The scales used to measure the variables in this study are the Orientation to Happiness Scale, the Personal Support Evaluation List (ISEL), and the Indonesian version of the Self-Empathy Scale (SWD). Based on the results of this study, social support, and self-compassion influence happiness by 27.4%. In addition, based on the results of this study of seven variables, four significantly impact happiness, namely evaluation of support, concrete support, self-kindness, and common humanity. This research contributed to the Positive Psychology field and gave parents and teachers feedback on supporting student happiness.